Emmy Sachs papers - Sachs, Emmy.
Letters to Sachs from Ernest Jones (1915 September 15) and Carl Spitteler (no year July 4), an undated analysis of a dream by Sachs, and envelope addressed by Sachs (1959).
Psychoanalyst.
In German and English.
Forms part of: Sigmund Freud collection.
Keywords: Jones, Ernest, -- 1879-1958 -- Correspondence; Spitteler, Carl, -- 1845-1924 -- Correspondence; Dream interpretation; Psychoanalysis; Psychoanalysts